Formulation of flakes with red kidney bean and red palm oil as a potential instant breakfast for type 2 diabetes - Riantiningtyas, Reisya Rizki; Sri Anna Marliyati, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Diabetes is a metabolic syndrome characterized by hyperglycaemia and the number of people with diabetes continues to increase significantly in the last thirty years. Red kidney bean (RKB) and red palm oil (RPO) have potential properties which may be beneficial for managing diabetes. Empirical data suggest that RKB contains alpha-glucosides inhibitors and alpha-amylase inhibitors while RPO contains antioxidant. This study was aimed to formulate flakes with red kidney bean and red palm oil as a potential instant breakfast for type 2 diabetes. The flakes were formulated with different ratios of RKB flour to corn flour (30:70, 40:60, 50:50, 60:40, and 70:30) while the addition of RPO was the same in all formulas (7.5 g in 205 g mixture). The selected formula based on the sensory evaluation was F1 (30:70), with the acceptability level of 87%. The nutrient content of the selected product was analysed using proximate methods and resulted as follows: 5.8% (w/w) moisture, 0.6% (d/w) ash, 13.2% (d/w) protein, 16.5% (d/w) fat, 69.6% (d/w) carbohydrate, 10% (d/w) fibre. One serving size of the developed flakes (55 g) consumed along with milk provided 18% of the energy requirement as well as 23% fat, 21% protein, and 15% carbohydrates from the total daily requirements and has high fibre content. These findings suggest that the selected product is potentially suitable as an alternative ready-to-eat breakfast meal for people with diabetes.